2008
DOI: 10.1007/s00520-008-0410-8
|View full text |Cite
|
Sign up to set email alerts
|

Noncancer life stresses in newly diagnosed cancer

Abstract: Noncancer life stresses are common among newly diagnosed cancer patients and have impact on QOL, and thus they should be taken into account in cancer care. Screening for noncancer life stresses may offer means to enhance QOL outcomes in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 38 publications
0
24
2
Order By: Relevance
“…When their effect on survival has been researched in isolation, no associations or negligible ones have been found [1,4,12]. However, life stressors have an impact on quality of life of cancer patients [9,14,21,22,24,25]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When their effect on survival has been researched in isolation, no associations or negligible ones have been found [1,4,12]. However, life stressors have an impact on quality of life of cancer patients [9,14,21,22,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Life events comprise stressors in the external or internal environment that may produce a stress or adaptation response [13,18,20]. Negative, undesirable events are important for health outcomes [9,13,14,21,22]. The psychobiological process in cancer [2,23] is supposed to be mediated by personal (including coping), medical, social, and life stress variables, and result in quality of life and survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, newly diagnosed cancer patients reported that in the years preceding the cancer diagnosis they experienced acute and chronic life stresses as well as loss events and previous chronic illness. 62 The data demonstrating the role for psychological stress in the development of pathologies of aging and cancer are of special interest and importance. They indicate that natural approaches including stress management have the potential to influence the molecular pathways of aging, aging-associated disorders, and cancer.…”
Section: The Role Of Psychological Stressmentioning
confidence: 99%
“…Many of the patients diagnosed with PCa choose to undergo surgical treatment. The anxiety of cancer diagnosis coupled with the side effect profile associated with surgical treatment impact the male's Clinical Urology Clinical Urology psychological state (2,3). Prostate cancer surgery will result in variable degrees of impaired urinary control and sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%